Pengaruh Penerapan Teori Kognitif David Ausubel Terhadap Hasil Belajar Nahwu Siswa Madrasah Diniyah Nurul Huda Malang - Asrori, Abdulloh; Imam Asrori; Kholisin (Universitas Negeri Jakarta, 2025)
This study aims to determine the effect of applying David Ausubel's cognitive theory on students' Nahwu learning outcomes at Madrasah Diniyah Nurul Huda Malang. The research used a pre-experimental design with one group pre-test and post-test. The subjects were 20 students who received learning treatment based on Ausubel's cognitive theory. Data were collected through pre-test and post-test results and analyzed using the Wilcoxon test. The findings revealed a significant improvement in students' Nahwu learning outcomes after applying Ausubel's cognitive theory, as indicated by the Wilcoxon test (Z = -3.738, Asymp. Sig. (2-tailed) = 0.000 < 0.05). These results suggest that integrating meaningful learning principles enhances students' ability to connect new knowledge with prior understanding, thereby improving conceptual mastery in Nahwu. Theoretically, this study reinforces Ausubel's claim that prior knowledge is a key determinant in cognitive development. Pedagogically, the findings encourage Arabic language educators to design learning experiences that activate students' existing knowledge structures to achieve deeper, more sustainable learning outcomes.